The Future of Democracy - Glassman, Ronald M. (Springer International Publishing : Imprint: Springer, 2019)
This book focuses on the processes that help stabilize democracy. It provides a socio-historical analysis of the future prospects of democracy. The link between advanced capitalism and democracy is emphasized, focusing on contract law and the separation of the economy from the state. The book also emphasizes the positive effects of the scientific world view on legal- rational authority. Aristotle's theory of the majority middle class and its stabilizing effect on democracy is highlighted. This book describes the face to face democracies of the past in order to give us a better perspective on the high tech democracies of the future, making it appealing to students and academics in the political and social sciences.